Optimal Retirement Wealth Allocation under Volatile Interest Rates: A GARCH-Based Analysis - Manasi Goral; A. S. Talawar (International Journal of Scientific Research in Science and Technology, 2025)
Managing post-retirement wealth effectively is crucial for ensuring financial security in uncertain market conditions. Traditional pension investment models assume constant interest rates, which fail to capture real-world financial volatility. This study develops an optimal investment strategy for post-retirement wealth management under stochastic interest rates, modeled using EGARCH and GJR-GARCH frameworks. By leveraging GARCH-type models, we estimate volatility dynamics and optimize asset allocation strategies. The Hamilton-Jacobi-Bellman (HJB) equation is applied within a stochastic control framework to derive the optimal investment policy. Sensitivity analysis is conducted to assess the impact of different risk aversion levels on portfolio allocation. The results demonstrate that accounting for stochastic interest rate volatility improves wealth sustainability in the post-retirement phase.
Keywords: GARCH models; HJB equation; Optimal asset allocation; Pension wealth management; Stochastic interest rates